Barriers Faced by Students in Writing Hortatory Exposition Texts - Wardani, Happy Kusuma; Ichsantin, Nur Afifah; Alimin; Hidayah, Bariqotul (ENGLISH JOURNAL OF INDRAGIRI, 2026)
Writing hortatory exposition texts poses considerable challenges for EFL students, particularly at the senior high school level. This study aimed to investigate the barriers faced by XI-1 students at SMAN 1 Sidayu in composing hortatory exposition texts and identify the factors influencing their writing performance. Using a descriptive quantitative approach, data were collected through students’ writing tasks and questionnaires administered to 32 participants. The research involved analysing students’ written texts and administering a questionnaire to uncover both internal and external factors. The results revealed that students struggled most with constructing arguments and applying accurate grammar, despite reporting high levels of self-motivation. Furthermore, external support from family, school, and the surrounding environment was perceived as minimal.